The Vocal Repertoire of Adult and Neonate Giant Otters (Pteronura brasiliensis) - Mumm, Christina A. S. (PLoS One, 2014)
Animals use vocalizations to exchange information about external events, their own physical or motivational state, or about individuality and social affiliation. Infant babbling can enhance the development of the full adult vocal repertoire by providing ample opportunity for practice. Giant otters are very social and frequently vocalizing animals. They live in highly cohesive groups, generally including a reproductive pair and their offspring born in different years. This basic social structure may vary in the degree of relatedness of the group members. Individuals engage in shared group activities and different social roles and thus, the social organization of giant otters provides a basis for complex and long-term individual relationships. We recorded and analysed the vocalizations of adult and neonate giant otters from wild and captive groups. We classified the adult vocalizations according to their acoustic structure, and described their main behavioural context. Additionally, we present the first description of vocalizations uttered in babbling bouts of new born giant otters. We expected to find 1) a sophisticated vocal repertoire that would reflect the species’ complex social organisation, 2) that giant otter vocalizations have a clear relationship between signal structure and function, and 3) that the vocal repertoire of new born giant otters would comprise age-specific vocalizations as well as precursors of the adult repertoire. We found a vocal repertoire with 22 distinct vocalization types produced by adults and 11 vocalization types within the babbling bouts of the neonates. A comparison within the otter subfamily suggests a relation between vocal and social complexity, with the giant otters being the socially and vocally most complex species.